2020
DOI: 10.1037/xge0000651
|View full text |Cite
|
Sign up to set email alerts
|

Is this my group or not? The role of ensemble coding of emotional expressions in group categorization.

Abstract: When exposed to others' emotional responses, people often make rapid decisions as to whether these others are members of their group or not. These group categorization decisions have been shown to be extremely important to understanding group behavior. Yet, despite their prevalence and importance, we know very little about the attributes that shape these categorization decisions. To address this issue, we took inspiration from ensemble coding research and developed a task designed to reveal the influence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…If bias in attention drives amplification among individuals with social anxiety, training these individuals to focus their attention on less expressive members of the crowd may be useful in reducing their social anxiety (e.g., Bauer, 2009). In conclusion, this project extends recent attempts to examine the role of ensemble coding in processes that are important to social functioning (Goldenberg et al, 2020;Lamer et al, 2018;Phillips et al, 2018). Learning more about how people rapidly evaluate complex social information not only may explain important aspects of social behavior but also may open the door to future interventions.…”
Section: Limitations and Future Directionsmentioning
confidence: 72%
“…If bias in attention drives amplification among individuals with social anxiety, training these individuals to focus their attention on less expressive members of the crowd may be useful in reducing their social anxiety (e.g., Bauer, 2009). In conclusion, this project extends recent attempts to examine the role of ensemble coding in processes that are important to social functioning (Goldenberg et al, 2020;Lamer et al, 2018;Phillips et al, 2018). Learning more about how people rapidly evaluate complex social information not only may explain important aspects of social behavior but also may open the door to future interventions.…”
Section: Limitations and Future Directionsmentioning
confidence: 72%
“…If bias in attention drives amplification among individuals with social anxiety, training these individuals to focus their attention on less expressive members of the crowd may be useful in reducing their social anxiety (see for example Bauer, 2009). To conclude, this project extends recent attempts to examine the role of ensemble coding in processes that are important to social functioning (Goldenberg et al, 2019;Lamer, Sweeny, Dyer, & Weisbuch, 2018;Phillips, Slepian, & Hughes, 2018). Learning more about how people rapidly evaluate complex social information may not only explain important aspects of social behavior, but may also open the door to future interventions.…”
Section: Limitations and Future Directionsmentioning
confidence: 84%
“…Established initially for low-level features of objects (e.g., size, brightness, orientation, speed, location; Alvarez & Oliva, 2008 ; Ariely, 2001 ; Bauer, 2009 ; Parkes et al, 2001 ; Watamaniuk & Duchon, 1992 ), ensemble coding has been shown to extend to higher-order person-related percepts, including judgements of emotion, identity, and sex (Alt et al, 2017; De Fockert & Wolfenstein, 2009 ; Goldenberg et al, 2020 ; Goodale et al, 2018 ; Haberman & Whitney, 2007 ; Yang & Dunham, 2019 ). For example, with regard to group membership, people can readily estimate the sex-based composition of briefly presented facial arrays ( Yang & Dunham, 2019 ).…”
Section: Person and People Perceptionmentioning
confidence: 99%